THE PLACE AND SIGNIFICANCE OF NON-VISUCOUS FLUID DYNAMICS IN TEACHING THE SCIENCE OF HYDRAULICS - Eshev Sabir Samatovich; Nazarov Odil Omankulovich (American Journals, 2023)
Looking back over the years, we have a deeper understanding of the value of our independence. We are going through a period of complete renewal in education, a real transition to a new process and adaptation to it. The subject of non-viscous fluids is very important in teaching hydraulics to students. Non-viscous fluids do not experience internal friction. A non-viscous fluid is a fluid model, an idealized environment that is not found in nature or technology. However, this idealized environment is of great importance in the study of the laws of dynamics.
Keywords: Hydraulics, viscosity, fluid dynamics, fluid motion, hydromechanics, fluid motion methods, Euler method, etc.